Economía circular: un camino hacia un Quito más sostenible - Arroyo Morocho, Flavio Roberto (2018)
This article shows the importance of Circular Economy today and how it should be implemented in companies in the city of Quito to build a radical change in our economic system and our environment. The last 150 years of industrial evolution have been dominated by a linear production and consumption model, where products / goods are produced from raw materials, then sold, used and finallydisposed of as waste. Faced with the current global economy and the increase in evidence pointing to the growing scarcity and overexploitation of resources, the need arose to search for a new economic model (business). The circular economy presents a radical change to achieve a sustainable economy for society, prioritizing the care and use of resources, reducing the environmental impact that we generate. Finally, the current situation of the Ecuadorian industry is analyzed, which seeks to change from a linear model to a circular model, trying to minimize risks, costs and environmental impacts.